2023
DOI: 10.1051/e3sconf/202336401002
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of treated wastewater reuse for irrigation: growth potential and development of lettuce in Al Hoceima province, Morocco

Abstract: The reuse of treated wastewater for agricultural practices is becoming increasingly important due to the growing demand for the transition to a circular economy. It has the major advantage of providing an alternative resource to the conventional water used for agricultural irrigation. The main objective of this work is to study, through tests on experimental installations, the effect of the type of irrigation water on the growth and development of lettuce. The types of irrigation water were prepared from purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These results align with the findings reported by Lahmani et al (2015), which demonstrated that the inclusion of mineral supplements in treated wastewater enhances coriander plant productivity. Similarly, Bel Haj et al (2023) and Urbano et al (2017) observed that incorporating mineral fertilizers into treated wastewater promoted growth parameters in lettuce.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These results align with the findings reported by Lahmani et al (2015), which demonstrated that the inclusion of mineral supplements in treated wastewater enhances coriander plant productivity. Similarly, Bel Haj et al (2023) and Urbano et al (2017) observed that incorporating mineral fertilizers into treated wastewater promoted growth parameters in lettuce.…”
Section: Resultsmentioning
confidence: 90%
“…In January 2018, a rehabilitation and restructuring project was initiated to increase the nominal flow from 4616 to 10,800 m 3 /d. The plant has a potential of irrigating 150,000 ha À1 yr À1 and spans a zone of 18 ha (Bel Haj et al, 2023). The employed treatment method encompasses biological treatment using activated sludge with a low organic load, incorporating microfiltration, and subsequent disinfection utilizing downstream ultraviolet light.…”
Section: Experimental Locationmentioning
confidence: 99%
“…The agricultural industry contributes significantly to water waste, as watering and harvesting crops consume substantial amounts of water [14], [15]. This level of water consumption can be classified as a waste that needs to be addressed, as clean water resources are essential for people's daily lives, not just for agriculture.…”
Section: Introductionmentioning
confidence: 99%